Bile secretory function in the obese Zucker rat: evidence of cholestasis and altered canalicular transport function. Issue 12 (11th November 2004) - Pizarro, M; Balasubramaniyan, N; Solís, N; Solar, A; Duarte, I; Miquel, J F; Suchy, F J; Trauner, M; Accatino, L; Ananthanarayanan, M; Arrese, M
Abstract : Background: Obese Zucker rats (ZR) have been used as an experimental model for non-alcoholic fatty liver disease and are particularly susceptible to various types of liver injury. Bile secretory function has not been assessed in ZR. Aim: To study bile secretion and expression of the main hepatobiliary transporters in ZR. Methods: Bile flow and biliary secretion of lipids and glutathione were determined in eight and 14 week old obese ZR and their lean controls. Protein mass and mRNA of the Na + /taurocholate cotransporting polypeptide (Ntcp), the bile salt export pump (Bsep), and the multidrug resistant associated protein 2 (Mrp2) were assessed by western and northern blot, respectively. The effects of administration of a tumour necrosis factor α inactivator (etanercept) and an insulin sensitiser (rosiglitazone) were assessed in obese ZR while leptin was given to non-obese rats to study its effect on Mrp2 expression. Results: ZR exhibited increased body weight and hyperlipidaemia. Only 14 week old obese ZR has fatty liver. Decreased bile flow and biliary lipid and glutathione secretion as well as reduced hepatic transport of both taurocholate and bromosulphthalein were found in obese ZR. Hepatic Mrp2 protein mass was markedly reduced (−70%) in obese rats while Ntcp and Bsep protein levels were similar to lean rats. Downregulation of Mrp2 seems to involve both transcriptional and post-transcriptional mechanisms probably related to insulin and leptin resistance. Conclusions: Obese ZR exhibit an impaired bile secretory function with significant functional and molecular alterations consistent with mild cholestasis. A defective hepatobiliary transport capacity may be a contributory factor in rendering the obese ZR more susceptible to liver injury.